Electricity requirements for a digital society - Baer, Walter S. (Rand, 2002)
Increasing use of the Internet and other information and communications technologies (ICTs) marks a U.S. transition toward a "digital society" that may profoundly affect electricity supply, demand and delivery. RAND developed four 20-year scenarios of ICT evolution (2001?2021) for the U.S. Department of Energy and assessed their implications for future U.S. electricity requirements. Increased power consumption by ICT equipment is the most direct and visible effect, but not necessarily the most important. Over time, the effects that ICTs have on energy management, e-commerce, telework, and related trends will likely be much more consequential. Even large growth in the deployment and use of digital technologies will only modestly increase U.S. electricity use over the next two decades. The more pressing concern for an emerging digital society will be how to provide the higher-quality and more-reliable power that ICTs demand